The association of blood pressure and hypertension with genetic markers identified in genome-wide association studies - S. K. Malyutina; V. N. Maksimov; P. S. Orlov; E. V. Mazdorova; A. N. Ryabikov; Yu. P. Nikitin; M. I. Voevoda (Российский кардиологический журнал, 2018)
Genetic background of hypertension (AT) and blood pressure (BP) regulation is extensively investigated in genome-wide association studies (GWAS). The findings from recent GWAS require replication in independent samples.Aim. To investigate the association between BP and AT in Russian population and several single nucleotide polymorphisms identified in GWAS.Material and methods. In the frame of “case-control” design we recruited subjects with AT diagnosed at age below 50 according to the criteria of BP >140/90 mm Hg and/or receiving antihypertensive therapy, and subjects with normotension according to 2 examinations from population sampling, Novosibirsk, totally included 514, men/women aged 45-69 years). From published GWAS we selected 24 genetic markers related to hypertension, 8 markers were included for present analysis (rs 13082711, rs1173771, rs13107325, rs3918226, rs1799945, rs805303, rs1458038, rs932764). Standard epidemiological methods were used (BP measurement, anthropometry, medical history of AT and treatment, risk factors of AT, socio-demographic parameters). Single nucleotide polymorphisms (SNPs) were tested using real time PCR.Results. In studied sample we replicated the association between rs3918226 (promoter region of gene of endothelial NO synthase; eNOS) and systolic BP (T-allele carriers had 9 mm Hg higher systolic BP than CC carriers in men, p=0,049 independent of age). New association was found between rs 932764 (gene of phospholipase-c-epsilon-1 isoform, PLCE1) and AT (heterozygotes genotype AG was protective in men, p=0,017 independent of age and body mass). The association between rs13107325 (gene of soluble carrier family 39/zinc transporter/member 8, SLC39A8) and systolic BP was confirmed (in men, С-allele carriers had higher systolic BP values then TT carriers, p=0,044, multivariable adjusted).Conclusion. In analysis of relationship between phenotypes of BP and AT and 8 genetic markers of AT in Russian population sample we replicated two known associations, revealed new association and identified new data on modulating effect of sex and body mass. These replications in newly studied Siberian population, different from early studied populations by risk factors profile, climate, geographic and other parameters, support the involvement of identified or close loci in potential mechanisms of AT susceptibility.